2018
DOI: 10.2478/jcbtp-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Expectations in Turkey: Determinants and Roles in Missing Inflation Targets

Abstract: This paper aims at specifying the determinants of 12-month ahead and 24-month ahead inflation expectations in Turkey by using monthly data from April 2006 to December 2016. Put differently, this paper tries to shed light on how inflation expectations respond to changes in past inflation rate, inflation target, output gap, USD/TL exchange rate, oil price, and EMBI in Turkey. To this end, the paper first conducts unit root tests in order to detect the order of integration of the variables. Then, the paper employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…In contrast, the inability of monetary authorities in forecasting inflation could be in the presence of high ERPT into domestic prices. The positive relationship between the expected inflation rate and exchange rate leads the success of inflation targeting strategy (Bulut, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, the inability of monetary authorities in forecasting inflation could be in the presence of high ERPT into domestic prices. The positive relationship between the expected inflation rate and exchange rate leads the success of inflation targeting strategy (Bulut, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As stated in Kara et al (2017a) and Kara et al (2017b), inflation expectations also increase during periods of the rise in exchange rates. As in Bulut (2018), it is confirmed that the USD / TL exchange rate is an effective factor on inflation expectations.…”
Section: Empirical Findingsmentioning
confidence: 61%
“…Bu çalışmalarda kredibilite düzeyi hakkında nicel bir sayı elde edilmemekte, sadece belirli bir dönem için TCMB'nin kredibiliteye sahip olup olmadığı sonucuna ulaşılmaktadır. TCMB'nin kredibilitesine ilişkin farklı dönemlere ait bulgular, kredibilite kaybı olduğunu (Başkaya vd., 2008;Çiçek ve Akar, 2014), kredibilitenin zaman içinde arttığını (Başkaya vd., 2010;Çiçek vd., 2011;Başkaya vd., 2012), kredibilitenin zaman ufkuna bağlı olarak değiştiğini (Bulut, 2018) ve kredibilitenin zaman içinde azaldığını (Çakmaklı ve Demiralp, 2020) göstermiştir. Bunun yanı sıra Bulut (2020) TCMB'nin kredi boşluğunun rassal yürüyüş davranışı içinde olduğu ve incelenen dönemde TCMB'nin kredibilite kaybı yaşadığı sonucuna ulaşmıştır.…”
Section: Introductionunclassified